Enhancing Student Learning Engagement through Role-Play Method in 5th Grade Indonesian Language Primary Classroom - Putri, Destari Dwi; Susanti, R. Hariyani; Herlinda, Herlinda; Aramudin, Aramudin (Journal of Learning Improvement and Lesson Study, 2024)
Indonesian language learning aims to improve students’ communication skills in both spoken and written Indonesian, while also fostering an appreciation for Indonesian literature. Elementary school (SD) students need to develop oral and written communication skills, as well as an appreciation for literary works. However, observations at SD Negeri 5 Lubai revealed a lack of interest in learning among most students, with 10 out of 29 students scoring below 75, falling short of the minimum passing grade. This research focuses on addressing the problem of speaking ability in Grade V students by introducing the role-play method. Role-playing involves students portraying different characters to explore relationships, feelings, attitudes, values, and problem-solving strategies. By actively engaging in role-play, students can develop their imagination, appreciation, and communication skills. The research conducted two cycles of activities, with an average learning outcome completeness of 34.48% in cycle I. In cycle II, there was a significant improvement, with a completeness percentage of 86.21%. These findings demonstrate the effectiveness of the role-play method in enhancing student learning engagement and improving their proficiency in Indonesian language skills.